Serial measurements of apoptotic cell numbers provide better acceptance criterion for PBMC quality than a single measurement prior to the T cell assay - Wunsch, Marie; Caspell, Richard; Kuerten, Stefanie; Lehmann, Paul V.; Sundararaman, Srividya (Cells, 2015)
As soon as Peripheral Blood Mononuclear Cells (PBMC) are isolated from whole blood, some cells begin dying. The rate of apoptotic cell death is increased when PBMC are shipped, cryopreserved, or stored under suboptimal conditions. Apoptotic cells secrete cytokines that suppress inflammation while promoting phagocytosis. Increased numbers of apoptotic cells in PBMC may modulate T cell functions in antigen-triggered T cell assays. We assessed the effect of apoptotic bystander cells on a T cell ELISPOT assay by selectively inducing B cell apoptosis using α-CD20 mAbs. The presence of large numbers of apoptotic B cells did not affect T cell functionality. In contrast, when PBMC were stored under unfavorable conditions, leading to damage and apoptosis in the T cells as well as bystander cells, T cell functionality was greatly impaired. We observed that measuring the number of apoptotic cells before plating the PBMC into an ELISPOT assay did not reflect the extent of PBMC injury, but measuring apoptotic cell frequencies at the end of the assay did. Our data suggest that measuring the numbers of apoptotic cells prior to and post T cell assays mayprovide more stringent PBMC quality acceptance criteria than measurements done only prior to the start of the assay.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Acceptance; Apoptosis; ELISPOT; T cell assay; Viability